2012
DOI: 10.1186/1475-2859-11-127
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of phosphoenolpyruvate:sugar phosphotranferase system and pyruvate kinase isozymes inactivation in central carbon metabolism flux distribution in Escherichia coli

Abstract: BackgroundIn Escherichia coli phosphoenolpyruvate (PEP) is a key central metabolism intermediate that participates in glucose transport, as precursor in several biosynthetic pathways and it is involved in allosteric regulation of glycolytic enzymes. In this work we generated W3110 derivative strains that lack the main PEP consumers PEP:sugar phosphotransferase system (PTS-) and pyruvate kinase isozymes PykA and PykF (PTS-pykA- and PTS-pykF-). To characterize the effects of these modifications on cell physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 56 publications
5
54
0
Order By: Relevance
“…This is consistent with the previous recognition that PykF is the main pyruvate kinase in E. coli (25,26). However, under anaerobic conditions, the activity of PykF accounted for 70% of the total pyruvate …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the previous recognition that PykF is the main pyruvate kinase in E. coli (25,26). However, under anaerobic conditions, the activity of PykF accounted for 70% of the total pyruvate …”
Section: Resultssupporting
confidence: 93%
“…In the aerobic glycolysis pathway of E. coli, PykF is believed to be the major contributor of pyruvate kinase activity, while PykA contributes little (25,26). Our enzymatic assay confirmed that PykA does contribute very little (7%) to total pyruvate kinase activity (Table 4).…”
Section: Discussionsupporting
confidence: 68%
“…A knock-out of the phosphotransferase system is known in the literature (Escalante et al, 2012) allowing a change of glucose uptake mechanism especially if combined with overexpression of hexose permease (Hernandez-Montalvo et al, 2003). Also, combinations of PTS and PYK knock-out (Lee et al, 2005) have been applied successfully, especially in respect to the production of AAAs (Gosset et al, 1996, Meza et al, 2012, Papagianni, 2012. Also very recently the knock-out of PTS and PYK by means of ptsH, ptsI, crr, and pykF has been described and applied for ccMA production from pHBA (Sengupta et al, 2015).…”
Section: Metabolic Peculiarities Of E Coli Hinder Knock-out Strategiesmentioning
confidence: 99%
“…Furthermore, PTS inactivation revealed a carbon recycling response between PEP and OAA combined with a reduced glycolytic flux. When these strains were transformed with plasmids encoding enzymes to promote the production of L-PHE, a 19-, 14-, and 25-fold increase on the yield of this amino acid was observed for the PTS, PTS − pykA, and PTS − pykF mutants, respectively [33]. Targeted proteomics and metabolite profiling analyses are also very valuable to provide feedback about expression systems used in the production of AAA.…”
Section: (S)-reticuline ((1s)-1-[(3-hydroxy-4-methoxyphenyl)methyl]-6mentioning
confidence: 99%
“…Additionally, high PEP availability has been achieved by modulation of the carbon flux from PEP to the TCA caused by the inactivation of one or both of the PYR kinases [33,34], as well as improving the recycling of PYR to PEP by a plasmid-encoded copy of PEP synthetase [35][36][37]. The overexpression of pckA, in combination with an enhanced carbon flow through the glyoxylate shunt, has also been proposed as a strategy to increase the yield of aromatic compounds [38,39].…”
Section: Introductionmentioning
confidence: 99%